Manchester system brachytherapy simulation using EGSnrc Monte Carlo simulation - Octavia, Shella Salsa; Sumaryada, Tony; Yani, Sitti (Indonesian Physics Communication, 2024)
One type of cervical cancer treatment is brachytherapy using the Manchester system. In this study, isodose curves were analyzed on tissue phantoms irradiated using several types of radioactive sources with the Manchester system using Monte Carlo simulation, EGSnrc. This study used a homogeneous tissue phantom with dimension 10 × 10 × 10 m3. The Manchester system uses 2 ovoid and 3 tandem containing radioactive sources placed inside the phantom. The resulting isodose curves were combined and analyzed using MATLAB-based VDOSE GUI. The results showed that the dose distribution for each type of radioactive source at the reference point had different values, namely Cobalt-60 had a dose distribution at reference point A of 15.08% with a dose distribution at reference point B of 0%, Cesium-137 was 13.37% and 0%, Iridium-192 was 13.27% and 0%. The use of radioactive source types can be adjusted to the actual location of cervical cancer.